Geometrical analysis for motion monitoring of rigid bodies with optical surface scanning in radiation oncology. (October 2021) - Dekker, Janita; van Wagenberg, Teun Pieter; de Smet, Mariska; Essers, Marion; Kusters, Martijn; de Kruijf, Willy
Highlights: Volume coverage instead of isocenter motion was used to assess intra-fraction motion. Source-voxel heat maps showed the amount of time a voxel was within a target volume. Target-voxel heat maps showed the time a voxel was at the 'target' voxel. Heat maps were used offline to give insight into clinical target volume motions. The method was applied to patient data of whole brain radiotherapy without a mask. Abstract: Background and purpose: Surface guided radiotherapy can be used to improve patient setup and for accurate intra-fraction motion monitoring in correspondence to the isocenter. For a clinical relevant motion analysis the actual displacement of the entire clinical target volume (CTV) is necessary. Therefore, the aim of this study was to develop a novel assessment method for intra-fraction motion for rigid body structures based on motion data and a geometrical analysis. Materials and methods: A threshold value on the volume coverage (VC(t)) of the CTV by the planning target volume (PTV) was proposed as online motion monitoring method. Moreover, offline analysis was performed by using heat maps and by calculating VCx, the volume coverage for at least x% of treatment time. The method was applied retrospectively to patient treatment data for whole brain radiation treatment without a thermoplastic mask. Results: In 132 out of 142 fractions in total the proportion of the CTV that was inside the PTV for at least 99% of the time (VC99) was more than 95%, for a CTV-to-PTV margin of 5 mm. The source-voxel heat map showed which part of the CTV had a reduced coverage and the target heat map showed the movement of the CTV. Conclusion: Instead of using an action threshold on the movements of the isocenter, a threshold on the VC(t) of the CTV by the PTV was proposed. The heat maps and resulting values of VCx can be used to adapt the VC(t) threshold or the CTV-to-PTV margin for subsequent fractions.